Injury and illness surveillance among Olympic athletes: Summary of the 2010 Winter, and the 2008 and 2012 Summer Olympic Games - Steffen, K.; Engebretsen, L. (Sports injuries and prevention, 2015)
Protection of the athletes` health is a clearly articulated objective of the International Olympic Committee (IOC). Longitudinal surveillance of injuries and illnesses can provide valuable data that may identify high-risk sports and disciplines. Such surveillance would build a foundation for introducing tailored preventive measures. During the XXIX (Beijing) and XXX (London) Summer Olympic Games and the XXI (Vancouver) Winter Olympic Games, comprehensive injury and illness recording by the medical staff of the participating National Olympic Committees and the sports medicine clinics at the different Olympic venues revealed that between 7 and 11 % of all athletes incurred an injury or suffered from at least one occurrence of illness during the Games. The incidence of injuries and illnesses varied substantially between sports. In the future, risk factor and injury mechanism analyses in high-risk Olympic sports are essential to better direct injury prevention strategies. Concomitantly, Periodic Health Evaluations of athletes would be instrumental in optimizing health protection.